Teaching-Learning - Davis, Harold S. (The Educational Forum, 1971)
Ways of Teaching by Ronald T. Hyman. Philadelphia: J. B. Lippincott Company, 1970. 283 pp. $3.95
0 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:A1971J589800042 tex.unique-id: [object Object]
Keywords: dept.edu

Nucleus of a unified curriculum - Clark, Jere W (Educational technology, 1971)
tex.unique-id: ISI:A1971Y118500007
Keywords: dept.edu; ⛔ No DOI found

Book Review: Principles of skill acquisition edited by e. a. bilodeau with the assistance of ina McD. bilodeau. new york: academic press, inc., 1969. 353 pp. 5.95 - Davis, Harold S (The Educational Forum, 1971)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/141-487-501-460-452 tex.type: [object Object]
Keywords: book.review; dept.edu